Clinical Validation of KRAS, BRAF, and EGFR Mutation Detection Using Next-Generation Sequencing. Issue 6 (1st June 2014) - Lin, Ming-Tseh; Mosier, Stacy L.; Thiess, Michele; Beierl, Katie F.; Debeljak, Marija; Tseng, Li-Hui; Chen, Guoli; Yegnasubramanian, Srinivasan; Ho, Hao; Cope, Leslie; Wheelan, Sarah J.; Gocke, Christopher D.; et al.
Abstract: Objectives: To validate next-generation sequencing (NGS) technology for clinical diagnosis and to determine appropriate read depth. Methods: We validated the KRAS, BRAF, and EGFR genes within the Ion AmpliSeq Cancer Hotspot Panel using the Ion Torrent Personal Genome Machine (Life Technologies, Carlsbad, CA). Results: We developed a statistical model to determine the read depth needed for a given percent tumor cellularity and number of functional genomes. Bottlenecking can result from too few input genomes. By using 16 formalin-fixed, paraffin-embedded (FFPE) cancer-free specimens and 118 cancer specimens with known mutation status, we validated the six traditional analytic performance characteristics recommended by the Next-Generation Sequencing: Standardization of Clinical Testing Working Group. Baseline noise is consistent with spontaneous and FFPE-induced C:G→T:A deamination mutations. Conclusions: Redundant bioinformatic pipelines are essential, since a single analysis pipeline gave false-negative and false-positive results. NGS is sufficiently robust for the clinical detection of gene mutations, with attention to potential artifacts.